Regulator of G‐protein signaling 5 regulates the shift from perivascular to parenchymal pericytes in the chronic phase after stroke. Issue 8 (2nd May 2019) - Roth, Michaela; Gaceb, Abderahim; Enström, Andreas; Padel, Thomas; Genové, Guillem; Özen, Ilknur; Paul, Gesine
ABSTRACT: Poststroke recovery requires multiple repair mechanisms, including vascular remodeling and blood‐brain barrier (BBB) restoration. Brain pericytes are essential for BBB repair and angiogenesis after stroke, but they also give rise to scar‐forming platelet‐derived growth factor receptor β (PDGFR‐β)‐expressing cells. However, many of the molecular mechanisms underlying this pericyte response after stroke still remain unknown. Regulator of G‐protein signaling 5 (RGS5) has been associated with pericyte detachment from the vascular wall, but whether it regulates pericyte function and vascular stabilization in the chronic phase of stroke is not known. Using RGS5‐knockout (KO) mice, we study how loss of RGS5 affects the pericyte response and vascular remodeling in a stroke model at 7 d after ischemia. Loss of RGS5 leads to a shift toward an increase in the number of perivascular pericytes and reduction in the density of parenchymal PDGFR‐β‐expressing cells associated with normalized PDGFR‐β activation after stroke. The redistribution of pericytes resulted in higher pericyte coverage, increased vascular density, preservation of vessel lengths, and a significant reduction in vascular leakage in RGS5‐KO mice compared with controls. Our study demonstrates RGS5 in pericytes as an important target to enhance vascular remodeling.—Roth, M., Gaceb, A., Enström, A., Padel, T., Genové, G., Özen, I., Paul, G. Regulator of G‐protein signaling 5 regulates the shift from perivascular to parenchymal pericytes in the chronic phase after stroke. FASEB J. 33, 8990–8998 (2019). www.fasebj.org